Therapeutic Efficacy of Chloroquine vs Artemether/lumefantrine Combination in Vivax Malaria in Nowshera and Surroundings (Medical Forum Monthly, 2022)
Objective: The study's main objective is to find the therapeutic Efficacy of chloroquine vs. artemether/lumefantrine combination in vivax malaria in Nowshera and its surroundings.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at department of medicine, CMH hospital, Nowshera, from June 2019 to January 2020.Materials and Methods: The data was collected from 121 patients with malaria. Total vivax-infected patients were divided in two groups. The Chloroquine group consisted of 62 patients, and Artemether/Lumefantrine group had 59 patients. All patients under investigation were male patients due to the non-availability of a facility for female admissions in the treatment centre. All study participants received the P. vivax infection treatment plan in accordance with national medication policy. The data was gathered and analyzed using SPSS 20.0. Each value was expressed as the mean SD.Results: The patient’s mean age was 29.39 years and range between 19 to 57 years. Both groups showed similar resolution in fever after 24 hours. Mean hemoglobin, bilirubin, ALT and ALP were 14.4 g/dl, 9.7 µmol/L, 45.2 U/L, and 168.2 IU/L respectively. After applying the chi-square test, the difference in response to treatment with Chloroquine and Lumefantrine/Artemether was insignificant (p-value=0.35). However, the mean time in resolution of symptoms was less in the Chloroquine group. No significant adverse effects were experienced with both treatments.Conclusion: It is concluded that there is no difference in response to treatment with Chloroquine and Lumefantrine/Artemeter for Vivax Malaria in the Nowshera and suburbs.